Investigations of Ballistic Characteristics of N340 Propellant - Radosław TRĘBIŃSKI (Badanie charakterystyk balistycznych prochu N340, 2017)
Results of investigations of ballistic characteristics of the single-based N340 propellant are presented. A novel approach, proposed in an earlier authors’ work, was applied. Basing on pressure records, obtained in closed vessel tests the burning law and the dynamic vivacity function were determined. High value of the exponent in the burning law was obtained (1.25). This effect can be attributed to the process of infiltration of hot gases into propellant pores, enhanced by the increase in the pressure. The dynamic vivacity function was proved to be dependent on the value of the loading density. A simple analytical approximation of the averaged vivacity function was proposed. It describes the ballistic properties of the propellant much better than the geometric law of combustion. An effect of heat losses on the vivacity function was estimated, showing relatively small influence of the losses on the vivacity function. The obtained results confirmed applicability of the novel approach to the characterization of ballistic properties of fined-grained propellants.
Keywords: Badania pirostatyczne prochu